Development and psychometric evaluation of the police quality of work-Life questionnaire - Zeinab Tabanejad; Fatemeh Oskouie; Abbas Ebadi; Morteza Mesri (Kashan University of Medical Sciences, 2020)
Background: Police staff have difficult work conditions, are prone to physical damages, and experience high levels of occupational stress. Their work-related problems may affect their quality of work life (QWL). Meanwhile, there is no appropriate instrument for assessing their WLQ. Objectives: This study was conducted to develop the police quality of work-life questionnaire (PQWLQ) and evaluate its psychometric properties. Methods: This methodological study was conducted in 2018-2019 in two phases. In the first phase, literature review and semi-structured interviews with 13 police staff were conducted and the results were used for item generation. In the second phase, the face, content, and construct validity and reliability of the questionnaire were assessed. For construct validity assessment through exploratory factor analysis, 234 police staff were purposefully recruited to fill out PQWLQ. Results: In the first phase, 57 items were produced. In the second phase, item number reduced to 38 after face and content validity assessment. In exploratory factor analysis for construct validity assessment, 14 more items were deleted and the remaining 24 items were loaded on two factors. The Cronbach's alpha and the test-retest intraclass correlation coefficient of PQWLQ were 0.947 and 0.931, respectively. Conclusion: The 24-item PQWLQ has acceptable validity and reliability and can be used for QWL assessment among police staff. The use of this scale can help police and health managers develop their understanding about police staff's QWL and develop strategies for its improvement.